2011
DOI: 10.1002/dmrr.1235
|View full text |Cite
|
Sign up to set email alerts
|

Pioglitazone may accelerate disease course of slowly progressive type 1 diabetes

Abstract: Pioglitazone may accelerate the disease course of SPIDDM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Metformin was used to treat five of the six patients in the S group at baseline; during the study period, the dosage was increased in two patients and was added in one patient (Table S2). We previously reported that metformin may suppress the disease course of SPIDDM/LADA more effectively than pioglitazone [ 23 ], and we subsequently experienced a patient with SPIDDM/LADA whose β-cell function was maintained for 5 years with treatment of metformin alone [ 37 ]. Metformin increases the GLP-1 level [ 38 ], which regulates lymphocyte proliferation and the maintenance of peripheral regulatory T cells [ 39 ]; given that metformin was recently reported to improve gut microbiome flora in type 2 diabetes patients [ 40 ], metformin treatment for non-insulin-dependent SPIDDM might have exerted immunomodulatory effects through gut flora modification.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Metformin was used to treat five of the six patients in the S group at baseline; during the study period, the dosage was increased in two patients and was added in one patient (Table S2). We previously reported that metformin may suppress the disease course of SPIDDM/LADA more effectively than pioglitazone [ 23 ], and we subsequently experienced a patient with SPIDDM/LADA whose β-cell function was maintained for 5 years with treatment of metformin alone [ 37 ]. Metformin increases the GLP-1 level [ 38 ], which regulates lymphocyte proliferation and the maintenance of peripheral regulatory T cells [ 39 ]; given that metformin was recently reported to improve gut microbiome flora in type 2 diabetes patients [ 40 ], metformin treatment for non-insulin-dependent SPIDDM might have exerted immunomodulatory effects through gut flora modification.…”
Section: Discussionmentioning
confidence: 99%
“…Because the inferiority of SU compared to insulin treatment had been revealed in the Tokyo study, pioglitazone, a thiazolidinedione (TZD) approved in Japan, was selected as the comparator. The efficacy of TZD on SPIDDM/LADA has been evaluated in several studies with conflicting results [ 23 , 24 ]. In addition, from an ethical point of view, patients under treatment with metformin were allowed to be enrolled because a possible favorable effect of metformin on SPIDDM/LADA was suggested in our previous study [ 23 ].…”
Section: Methodsmentioning
confidence: 99%
“…Studies conducted by Shimada et al (18) in adults with slowly progressive T1DM showed progression of disease in subjects treated with pioglitazone when compared to those receiving metformin. At two years post intervention, 3 of the 4 subjects in the pioglitazone group reached a HbA1c of 8% compared to 1 of 5 in the metformin group (18).…”
Section: Discussionmentioning
confidence: 98%
“…At two years post intervention, 3 of the 4 subjects in the pioglitazone group reached a HbA1c of 8% compared to 1 of 5 in the metformin group (18). Shimada et al (18) reported that pioglitazone accelerates disease progression, but this conclusion may have been impacted by the small sample size.…”
Section: Discussionmentioning
confidence: 99%
“…We need to compare insulin and metformin directly in a future study to confirm whether metformin really reduces the progression to an insulindependent state in SPIDDM patients. Regarding thiazolidinediones, which improve insulin resistance, several previous studies have reported the use of this drug in patients with SPIDDM (16)(17)(18); however, there is no consensus to date. Biguanides also improve insulin resistance and may preserve the insulin secretion capacity, although there are no reports regarding the clinical course of SPIDDM after using this class of drug.…”
Section: Discussionmentioning
confidence: 99%